The humanism that nests in the new religious education programs - Wielewski Narloch, Nelise (2025)
Costa Rica’s religious education program (2024) replaces the theological approach of the previous program (1994), with a person-centered anthropology grounded in Christian principles. It also incorporates intercultural and interreligious dialogue as a cross-cutting theme, responding to the cultural and religious diversity constitutionally recognized since 2015. This article reviews the anthropological perspective of the new program. The perspective of intercultural humanism is proposed so that religious education can help those involved in educational processes “travel, with the attitude of apprentices of humanity, the paths of humanization of the world’s cultural and religious traditions.”